Assessing the Open Method of Coordination: institutional design and national influence of EU social policy coordination (Basingstoke, 2014)
"Based on the findings of a large-scale, comparative research project, this book systematically assesses the institutional design and national influence of the Open Method of Coordination (OMC) on Social Inclusion and Social Protection, at the European Union (EU) level and in ten EU Member States. Besides offering novel empirical and theoretical insights into the operation and impact of the OMC, the book presents an up-to-date perspective on the future of social policy coordination within the Europe 2020 Strategy. The book is required reading for anyone concerned with understanding the contribution of new forms of governance to the past and future development of Social Europe."